FRI0401 The tyrosine phosphatase shp2 controls tgfΒ-induced stat3 signalling to regulate fibroblast activation and fibrosis. (12th June 2018) - Zehender, A.; Huang, J.; Györfi, A.-H.; Matei, A.-E.; Dees, C.; Beyer, C.; Gelse, K.; Ramming, A.; Bergmann, C.; Birchmeier, W.; Distler, O.; Schett, G.; et al.
Abstract : Background: SHP2, encoded by the PTPN11 gene, is a ubiquitously expressed non-receptor tyrosine phosphatase (PTP). Altered expression and activity levels of SHP2 have also been implicated into the pathogenesis of autoimmune diseases. Objectives: In our study, we aim to characterise the role of SHP2 as a possible novel molecular checkpoint of transforming growth factor-β (TGFβ)-induced JAK2/STAT3 signalling in fibrotic diseases. Methods: Mice carrying Shp2 fl/fl x Col1a2-Cre ER were generated to specifically knockout Shp2 in fibroblasts. SHP2 was inhibited using NSC-87877 inhibitor. The role of Shp2 was investigated in three different mouse models: Bleomycin- and TBRI CA induced dermal fibrosis as well as TSK1 genetic model of skin fibrosis. The construct pCMV3-Flag-JAK2 was used for overexpression and for in vitro mutagenesis of human JAK2. Co-immunoprecipitation was performed to confirm the interaction between SHP2 and JAK2. STAT3 activation was analysed by reporter assay. Protein and mRNA expression levels were analysed by Western Blot and qPCR. Results: Our data characterise SHP2 as an important regulator of TGFβ signalling in fibroblasts. Although SHP2 expression is decreased in systemic sclerosis (SSc), the moderate downregulation of SHP2 expression is not sufficient to counterbalance the hyper-activation of TGFβ signalling in SSc. However, Shp2 -deficient murine fibroblasts are less responsive to TGFβ. An impaired response to the profibrotic effects of TGFβ was also observed in human SSc fibroblasts with siRNA-mediated knockdown of SHP2 and upon pharmacological inhibition of SHP2. We show that SHP2 can dephosphorylate JAK2 at the inhibitory Y570 site to promote TGFβ-dependent activation of JAK2 and its downstream mediator STAT3. In contrast, pharmacologic inhibition of SHP2, overexpression of a catalytically inactive SHP2 mutant or knockout of SHP2 inhibits dephosphorylation of pJAK2 Y570 preventing phosphorylation of JAK2 at the activation site Y1007/Y1008 and subsequent activation of STAT3 in TGFβ-stimulated fibroblasts and in experimental fibrosis. Fibroblasts overexpressing SHP2 are more susceptible to the profibrotic effects of TGFβ, whereas the stimulatory effects of TGFβ on myofibroblast differentiation and collagen release are reduced in Shp2 knockout fibroblasts. In addition, fibroblast-specific inactivation of Shp2 in vivo protected from experimental fibrosis induced by overexpression of a constitutively active TGFβ receptor type I, by bleomycin injection and ameliorated fibrosis in TSK1 mice. Conclusions: The present study describes for the first time a role of SHP2 in the pathogenesis of SSc. SHP2 is required for the activation of JAK2 and STAT3 by TGFβ. Inactivation of SHP2 prevents fibroblast activation and tissue fibrosis, providing evidence that SHP2 may be a potential target for the treatment of fibrosis. Disclosure of Interest: A. Zehender: None declared, J. Huang: None declared, A.-H. Györfi: None declared, A.-E. Matei: None declared, C. Dees: None declared, C. Beyer: None declared, K. Gelse: None declared, A. Ramming: None declared, C. Bergmann: None declared, W. Birchmeier: None declared, O. Distler Grant/research support from: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, Roche/Genentech, Medac, Biovitrium, Boehringer Ingelheim, Novartis, 4D Science, Active Biotech, Bayer, Sinoxa, Serodapharm, EpiPharm, GSK, Pharmacyclics and Biogen, Consultant for: Actelion, Pfizer, Ergonex, BMS, Sanofi-Aventis, United BioSource Corporation, Roche/Genentech, Medac, Biovitrium, Boehringer Ingelheim, Novartis, 4D Science, Active Biotech, Bayer, Sinoxa, Serodapharm, EpiPharm, GSK, Pharmacyclics and Biogen, G. Schett: None declared, J. Distler Shareholder of: 4D Science GmbH, Grant/research support from: Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis and UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB